Analisis Komunikasi Persuasif Film 12 Angry Men (1957) Menggunakan Pendekatan Retorika Aristoteles Dalam Semiotika Roland Bhartes - Atiyya Vidia Falika; Ratna Setyarahajoe; Muhammad Fadeli (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study analyzes persuasive communication in the film 12 Angry Men (1957) directed by Sidney Lumet through the integration of Roland Barthes’ semiotic theory and Aristotle’s rhetorical approach. Using a qualitative descriptive method, this research examines key scenes, dialogues, body language, and visual elements to understand how persuasive meaning is constructed during jury deliberation. The findings reveal that signs operate at three levels: denotation, connotation, and myth. Denotatively, the film presents logical debate over trial evidence. Connotatively, it reflects themes of empathy, prejudice, and emotional tension. At the myth level, the narrative reinforces ideological concepts of justice, rationality, and moral responsibility. Rhetorical analysis shows that Juror #8 effectively employs ethos, pathos, and logos to influence other jurors without coercion. The integration of semiotics and rhetoric demonstrates how persuasive communication can transform attitudes and promote critical thinking within group decision-making contexts.